Disentangled emotions in blended learning. (1st January 2012) - Parlangeli, Oronzo; Marchigiani, Enrica; Guidi, Stefano; Mesh, Linda
Given the increasing attention to the important relationship between learning and emotions, the present study was conducted to investigate the emotional experience of students attending a blended learning course. The course was a blended English course designed for adult learners. 148 participants, drawn from two different populations, participated in the study. The emotions experienced by the subjects, both during the early face-to-face lessons and their first interactions with the online learning environment, were investigated by means of a questionnaire. Results show that the two learning environments can give rise to similar, but not identical, emotional experiences. However, such differences are related to emotions that keep their sign, this being positive or negative, in spite of the changing environment. In addition, correlational and factorial analyses suggest that the different emotional experiences manifested by specific categories of students do not depend on the environment only, but also on individual characteristics and contextual motivational factors.